Best Paper Selection (Yearbook of Medical Informatics, 2021)
Powell KR, Deroche CB, Alexander GL. Health Data Sharing in US Nursing Homes: A Mixed Methods Study. https://www.jamda.com/article/S1525-8610(20)30197-3/fulltext Cappetta K, Lago L, Potter J, Phillipson L. Under-coding of dementia and other conditions indicates scope for improved patient management: A longitudinal retrospective study of dementia patients in Australia. https://journals.sagepub.com/doi/abs/10.1177/1833358319897928?journalCode=himd Sheriffdeen A, Millar JL, Martin C, Evans M, Tikellis G, Evans SM. (Dis)concordance of comorbidity data and cancer status across administrative datasets, medical charts, and self-reports. https://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-020-05713-5